2021
DOI: 10.1093/cei/uxab023
|View full text |Cite
|
Sign up to set email alerts
|

The autoimmune encephalitis-related cytokine TSLP in the brain primes neuroinflammation by activating the JAK2-NLRP3 axis

Abstract: NLRP3 inflammasome hyperactivation contributes to neuroinflammation in autoimmune disorders, but the underlying regulatory mechanism remains to be elucidated. We demonstrate that compared with wild-type (WT) mice, mice lacking thymic stromal lymphopoietin (TSLP) receptor (TSLPR) (Tslpr -/- mice) exhibit a significantly decreased experimental autoimmune encephalitis (EAE) score, reduced CD4 + T cell infiltration, and restored myelin basic protein (MBP) expression in the brain after EAE induction by myelin oligo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Moreover, these mice display impaired differentiation of T cells into myelin oligodendrocyte glycoprotein-specific effector and memory T cells ( 123 ). Yu et al ( 124 ) showed that TSLP receptor-deficient ( Tslpr − / − ) mice also exhibit resistance to EAE. Moreover, they found that TSLPR signaling induces neuroinflammation by activating Janus kinase, which then hyperactivates the NLR family pyrin domain containing 3 inflammasome ( 124 ), which in turn drives systemic T H 1 and T H 17 inflammation and chemotaxis of immune cells to the CNS.…”
Section: Role Of Epithelium-derived Cytokines In Autoimmune Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these mice display impaired differentiation of T cells into myelin oligodendrocyte glycoprotein-specific effector and memory T cells ( 123 ). Yu et al ( 124 ) showed that TSLP receptor-deficient ( Tslpr − / − ) mice also exhibit resistance to EAE. Moreover, they found that TSLPR signaling induces neuroinflammation by activating Janus kinase, which then hyperactivates the NLR family pyrin domain containing 3 inflammasome ( 124 ), which in turn drives systemic T H 1 and T H 17 inflammation and chemotaxis of immune cells to the CNS.…”
Section: Role Of Epithelium-derived Cytokines In Autoimmune Diseasesmentioning
confidence: 99%
“…Yu et al ( 124 ) showed that TSLP receptor-deficient ( Tslpr − / − ) mice also exhibit resistance to EAE. Moreover, they found that TSLPR signaling induces neuroinflammation by activating Janus kinase, which then hyperactivates the NLR family pyrin domain containing 3 inflammasome ( 124 ), which in turn drives systemic T H 1 and T H 17 inflammation and chemotaxis of immune cells to the CNS. Thus, blocking TSLP signaling may be a prospective target for MS.…”
Section: Role Of Epithelium-derived Cytokines In Autoimmune Diseasesmentioning
confidence: 99%
“…In EAE, the expression levels of NLRP3 mRNA and protein were increased (Gris et al, 2010 ; Ke et al, 2017 ), and compared to the wild-type mice, Nlrp3 −/− mice showed reduced numbers of Th1 and Th17 cells in the spinal cord and peripheral lymphoid tissues and markedly mild EAE (Gris et al, 2010 ; Inoue et al, 2012a ). Recently, it was reported that thymic stromal lymphopoietin (TSLP) could directly induce NLRP3 expression through phosphorylation of Janus kinase (JAK) 2, and Tslpr −/− mice showed decreased NLRP3 expression and EAE scores (Yu et al, 2021 ). Zhang et al ( 2018 ) reported that a deficiency of microglial ASC could attenuate the expansion of T cells and the infiltration of neutrophil, which suggests the important role of ASC in EAE.…”
Section: Nlrp3 Inflammasome In the Pathogenesis/pathophysiology Of Msmentioning
confidence: 99%
“…Interestingly, TGFβ2 and BMP4 can act both synergistically and antagonistically in various settings and tissues 63 . DKK1 is a negative regulator of Wnt signaling 64 , while TSLP is a pleiotropic cytokine that has been traditionally implicated in T-cell maturation and proinflammatory immune responses 65 . Finally, NLGN1 is a postsynaptic cell adhesion molecule important for neuronal spinogenesis, synaptic formation, and even astrocyte morphogenesis 66 .…”
Section: Synergistic Mechanism Of Candidate Ligandsmentioning
confidence: 99%